2022
DOI: 10.1177/23779608221095432
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Innovative Work Behavior of Nurses Through Diversity Climate: The Mediating Role of Job Crafting

Abstract: Introduction Innovative work behavior of nurses is essential to deliver affordable quality healthcare services. Diversity climate and job crafting are a few of the supportive managerial strategies that can be applied to cultivate the innovative capacity of nurses. Objective Aim for the current study is to: (a) examine the role of diversity climate in cultivating innovative work behavior of nurses directly; and (b) indirectly through job crafting. Methods For this study data was collected through cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 86 publications
(175 reference statements)
0
4
0
Order By: Relevance
“…This study investigated the relationship between TL and nurses' JP using WE as a mediating variable and WEV as an intermediate moderating variable that influenced the relationship between the two variables and changed their direction or strength to stimulate mutual relationships between nurses. The intention was to optimize nurses' JP and transform their work practices into leadership practices (Baig et al, 2022). Riyanto et al (2021b) revealed that using a TL style in the workplace directly affected employee productivity in the service industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study investigated the relationship between TL and nurses' JP using WE as a mediating variable and WEV as an intermediate moderating variable that influenced the relationship between the two variables and changed their direction or strength to stimulate mutual relationships between nurses. The intention was to optimize nurses' JP and transform their work practices into leadership practices (Baig et al, 2022). Riyanto et al (2021b) revealed that using a TL style in the workplace directly affected employee productivity in the service industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In today’s extremely sensitive and modern environment, innovation is vital for the health sector’s survival and long-term competitive advantage [ 1 ]. Employees’ creative ideas and innovative potential have long been acknowledged as the process that drives organizational innovation at the individual level [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The growth of any organization especially healthcare ones depends on the innovative behavior of their employees. Nurses in particular must demonstrate innovative behaviors for a number of reasons, including the requirement to adapt to the shifting illness load such as covid-19, the fast technological advancements, novel care models and new communication and data processing approaches [ 1 ]. The ethical climate acts as a guide for staff members to understand the acceptable and unacceptable actions, assisting them in making more informed judgments.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses have been acknowledged as the backbone of healthcare systems as they play a fundamental role in taking care of patients and providing round the clock services. In fact, it is estimated that as much as 80% of care within a healthcare system is provided by nurses ( Baig et al, 2022 ). Nurses are natural innovators as they often introduce new approaches, ideas, and solutions to problems faced during the provision of care.…”
Section: Introductionmentioning
confidence: 99%